Epistimologi Barat Modern: Analisis Kritis terhadap Asas, Kelemahan dan Pengaruhnya terhadap Dunia Islam - Avid Rusyadi; Muhammad Muhammad; Abdul Azis; Muhammad Amri; Ari Ramadhanu Saputra; Hikmatunnazilah Hikmatunnazilah; Rina Setyaningsih (Pusat Riset dan Inovasi Nasional, 2025)
The foundations of Western epistemology are profoundly rooted in ancient Greek philosophy. Throughout its historical development, this epistemological tradition has been shaped by rational, secular, and value-neutral modes of thought. It has given rise to dominant paradigms such as rationalism, empiricism, critical philosophy, and intuitionism. While these paradigms differ in their methodologies and approaches to acquiring knowledge, they are all grounded in a shared philosophical outlook that prioritizes human reason and sensory experience. This study investigates the core aspects of Western epistemology, including its historical evolution, defining traits, inherent limitations, and adverse effects. The research adopts a qualitative method based on literature review and philosophical analysis, employing a systematic and reflective approach. Data were gathered from library sources and examined using various analytical tools, including interpretation, induction and deduction, coherence analysis, holistic reasoning, heuristics, and descriptive analysis. The study concludes that Western epistemology is characterized by an overreliance on rational and empirical methods, a dichotomous worldview, anthropocentrism, resistance to spiritual insight, perpetual doubt, secularism, and a dismissal of sacred values. These traits give rise to fundamental weaknesses such as extreme rationalism, a fragmented view of truth and reality, secularist ideology, and the elevation of humanism and existentialism as ultimate values. The impact of Western epistemology extends beyond the West, influencing Islamic intellectual traditions by encouraging secularization, liberalism, and the advancement of scientific disciplines that exclude recognition of divine authority.